How alcohol marketing engages users with alcohol brand content on Facebook: an Indian and Australian perspective - Gupta, H.; Pettigrew, S.; Lam, T.; Tait, Robert (Routledge, 2017)
Little work has been conducted to understand how alcohol marketers engage users with their brands’ Facebook pages in India and Australia. We aimed to evaluate and compare (i) the types of marketing techniques alcohol marketers utilize to facilitate user engagement on their brands’ Facebook pages and (ii) the extent to which users engage with these techniques in two diverse national contexts. We identified the ten most popular alcohol brands on Facebook in India and Australia based on the number of ‘likes’ for each official brand site. Brand websites and data analytic sources were accessed to collect metrics relating to number of likes, frequency of posts made by alcohol marketers on their brand websites and the resulting comments from fans, and messages relating to responsible drinking. The identified brands accrued substantial user engagement (e.g. Budweiser beer attracted 12.8 million likes in Australia and Foster’s beer 802,807 likes in India). The strategies employed were a mix of country-specific (e.g. India: inspirational talks and livelihood skills vs. Australia: posts related to the brand’s tradition or heritage) and generic approaches (e.g. alcohol sponsorship of sport, music, and fashion, offering consumption suggestions, organizing competitions, giveaways, and use of memes). This cross-national comparison illustrates that alcohol marketing on Facebook is user-focused and flexible, works with specific national contexts, and capitalizes on the cultural meanings users invoke in their interactions with sites. The study results also demonstrate the potential for brands to engage those under the legal drinking age by delivering alcohol content on Facebook.